1952
DOI: 10.1107/s0365110x52001787
|View full text |Cite
|
Sign up to set email alerts
|

The crystal and molecular structure of α-glucose

Abstract: The crystal structure of s-glucose has been fully determined. In the elucidation of the structure, extensive use was made of the two-dimensional Patterson function. The refinement of the atomic parameters was carried out by Fourier and least-squares methods.The stereochemical configuration of the molecule, as deduced on purely chemical grounds, has been directly confirmed. The pyranose ring is in the Sachse-lY[ohr trans form, and there is a c/sglycol grouping on C 1 and C~. Some attempt was made to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

1954
1954
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(33 citation statements)
references
References 3 publications
0
33
0
Order By: Relevance
“…The nature of these interactions is not known; however, glycan:glycan interactions involving intermolecular hydrogen bonding have been noted in simple glycan crystals, with sucrose known to have up to six intermolecular hydrogen bonds within a crystal (36), and glucose forming two hydrogen bonds in a glucose crystal (37). Chitin forms two interchain hydrogen bonds between the C=O and NH groups and/or the C6-OH of neighboring sugars (38).…”
Section: Discussionmentioning
confidence: 99%
“…The nature of these interactions is not known; however, glycan:glycan interactions involving intermolecular hydrogen bonding have been noted in simple glycan crystals, with sucrose known to have up to six intermolecular hydrogen bonds within a crystal (36), and glucose forming two hydrogen bonds in a glucose crystal (37). Chitin forms two interchain hydrogen bonds between the C=O and NH groups and/or the C6-OH of neighboring sugars (38).…”
Section: Discussionmentioning
confidence: 99%
“…The author has undertaken a detailed examination of the crystal structure of E-D-glucose as a preliminary to a study of other more complex cellulose oligosaccharides. McDonald & Beevers (1950, 1952 determined the crystal structure of a-D-glucose and more recently Killean, Ferrier & Young (1962) determined the structure of a-D-glucose monohydrate. Both structures showed that the pyranose ring possessed the Sachse trans configuration.…”
mentioning
confidence: 99%
“…The axial C(1)-O(1) bond is shorter than the usual C-O bond length by about 1-5 times the probable error and may be significant. Shortening of the axial C-OH bond on the l-position was observed by McDonald (1952) in a-D-glucose, though this has been queried by Killean, Ferrier & Young (1962). It was also observed by McGeachin (1957) character, though the precision of the determination is not high enough to warrant further discussion.…”
Section: Description Of the Structurementioning
confidence: 90%